A comprehensive atlas of epigenetic regulators reveals tissue-specific epigenetic regulation patterns. Issue 1 (31st December 2023) - Wang, Jilu; Shi, Aiai; Lyu, Jie
ABSTRACT: Epigenetic machinery contributes to gene regulation in eukaryotic species. However, the machinery including more than 600 epigenetic regulator (ER) genes responsible for reading, writing, and erasing histone modifications and DNA modifications remains largely uncharacterized across species. We compile a comprehensive list of ERs based on an evolutionary analysis across 23 species, which is the most comprehensive ER list in various species until recently. We further perform comparative transcriptomic analyses across different tissues in humans, mice, as well as other amniote species. We observe a consistent tissue-of-origin expression specificity pattern of duplicated ER genes across species and suggest links between expression specificity and ER gene evolution as well as ER function. Additional analyses further suggest that ER duplication can generate tissue-specific ER genes with the same epigenetic substrates, which may be closely related to their regulatory specificity in tissue development. Our work can serve as a foundation to better comprehend the tissue-specific expression patterns of ER genes from an evolutionary perspective and also the functional implications of ERs in tissue-specific epigenetic regulation.